Defining end of life in dementia: A systematic review. (December 2021) - Browne, Bria; Kupeli, Nuriye; Moore, Kirsten J; Sampson, Elizabeth L; Davies, Nathan
Background: Dementia is a life-limiting condition that affects 50 million people globally. Existing definitions of end of life do not account for the uncertain trajectory of dementia. People living with dementia may live in the advanced stage for several years, or even die before they reach the advanced stage of dementia. Aim: To identify how end of life in people with dementia is measured and conceptualised, and to identify the factors that contribute towards identifying end of life in people with dementia. Design: Systematic review and narrative synthesis. Data Sources: Electronic databases MEDLINE, EMBASE, PsychInfo and CINAHL, were searched in April 2020. Eligible studies included adults with any dementia diagnosis, family carers and healthcare professionals caring for people with dementia and a definition for end of life in dementia. Results: Thirty-three studies met the inclusion criteria. Various cut-off scores from validated tools, estimated prognoses and descriptive definitions were used to define end of life. Most studies used single measure tools which focused on cognition or function. There was no pattern across care settings in how end of life was defined. Healthcare professionals and family carers had difficulty recognising when people with dementia were approaching the end of life. Conclusion: End-of-life care and research that focuses only on cognitive and functional decline may fail to recognise the complexities and unmet needs relevant to dementia and end of life. Research and clinical practice should adopt a needs-based approach for people with dementia and not define end of life by stage of disease.